Ecocritical Analysis of J.G. Ballard’s The Drowned World: A Study of High School Students’ Insights - Oktaviansyah, Muhammad Eko (Journal of Language, Literature and Teaching, 2024)
This study applies Greg Garrard’s ecocritical theory to analyze J.G. Ballard's The Drowned World and explores twelfth-grade students' insights of its environmental themes at MAN 2 Rejang Lebong. Aiming to enhance students’ environmental literacy, it uses an integrated approach combining literary analysis with qualitative and quantitative methods. Ecological themes in the novel are explored alongside an assessment of students’ awareness and understanding of environmental issues. Data were collected through questionnaires completed by 40 students and semi-structured interviews with a subset of students post-reading. Findings indicate that The Drowned World—a portrayal of a post-apocalyptic world shaped by global warming—contains key ecocritical components such as wilderness, apocalypse, animals, dwelling, and the Earth. However, the mixed-methods analysis exhibits 80% of students faced challenges in understanding themes connecting to the components, due to language barriers, limited interest, and insufficient classroom discussion. Only 20% demonstrated an understanding of critical issues like climate change. These findings suggest that the novel alone may not effectively enhance environmental awareness. The study recommends contextual teaching and guided discussions to aid students in grasping ecological themes. Its contribution lies in integrating mixed methods and ecocritical approaches. Both strategies are very essential for promoting environmental literacy and advancing sustainability education.